PENERAPAN STRATEGI COOPERATIVE LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII G SMP NEGERI 1 BOBOTSARI DENGAN MATERI OPERASI BENTUK ALJABAR TAHUN PELAJARAN 2009/2010 - Puji Santosa (Khazanah Pendidikan, 2010)
This classroom action reasearch was aimed at improving student’s achievement and participation in following the topic of algebraic operation. There were two cycles each which consisted of four stages (palnning, acting, observation, and reflection). The result showed that cooperative learning gradually improved achievement from 70.87 at pre-cycle stage and 78.12 cycle I which then became 86.67 in cycle II. Besides that, student’s participation also improved from 12 students (33.33 %) at pre-cycle stage to 25 969.40 %in cycle I and 33 (83.33 %) in cycle II. Key words: Cooperative Learning, achievement, and student’s participation